2013
DOI: 10.1016/j.theriogenology.2013.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of postpartum suppression of ovulation on uterine involution in dairy cows

Abstract: The objective of this study was to investigate the effect of time of first postpartum ovulation after calving on uterine involution in dairy cows with and without uterine puerperal disease. Transvaginal follicular puncture (FP) of follicles >6 mm suppressed ovulation and development of a CL until Day 42 after calving. Fifty-three lactating Holstein Friesian cows (3.4 ± 1.2 years old, parity 2.5 ± 1.0 [median ± mean absolute deviation]) were divided into groups on the basis of the presence (UD+) or absence (UD−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
6
0
2
Order By: Relevance
“…This assumption is supported by reports from other researchers, such as Smith and Wallace (1998), who showed that cyclicity before 21 DIM resulted in lower pregnancy rates and greater days open. Moreover, some authors have indicated that neither naturally delayed timing to first estrus nor suppressed first ovulation influence final fertility (Sakaguchi et al, 2004;Heppelmann et al, 2013). Additionally, the same authors reported that delayed cyclicity accelerated uterine involution of postpartum dairy cows (Sakaguchi et al, 2004;Heppelmann et al, 2013), which agrees with our observation that TRT1 had fewer cows resuming cyclicity but smaller uterine body size on d 14 compared with TRT2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This assumption is supported by reports from other researchers, such as Smith and Wallace (1998), who showed that cyclicity before 21 DIM resulted in lower pregnancy rates and greater days open. Moreover, some authors have indicated that neither naturally delayed timing to first estrus nor suppressed first ovulation influence final fertility (Sakaguchi et al, 2004;Heppelmann et al, 2013). Additionally, the same authors reported that delayed cyclicity accelerated uterine involution of postpartum dairy cows (Sakaguchi et al, 2004;Heppelmann et al, 2013), which agrees with our observation that TRT1 had fewer cows resuming cyclicity but smaller uterine body size on d 14 compared with TRT2.…”
Section: Discussionsupporting
confidence: 90%
“…98 No. 9, 2015 possibly PGE 2 , which is known for its relaxing effect on myometrium contractions and immunosuppressive effect on uterine defenses that delays uterine involution (Sakaguchi et al, 2004;Heppelmann et al, 2013). Therefore, it is speculated that in the first 49 d after calving, PGF 2α -driven uterine involution is more crucial for the subsequent fertility.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of early resumption of ovarian cyclicity remains controversial. Some studies reported that early ovulation resulted in greater pregnancies per AI (P/AI) and shorter calving to conception interval (Galvão et al, 2010;Bittar et al, 2014); others, however, reported delayed uterine involution (Heppelmann et al, 2013) and detrimental effects on reproductive performance (Smith and Wallace, 1998). Sheldon et al (2006) proposed a case definition for clinical endometritis as the presence of purulent discharge detectable in the vagina at 21 d or more after parturition.…”
Section: Introductionmentioning
confidence: 99%
“…This agrees with what was observed in this study, where the interval labor-estrum (ILE) was longer in first-time cows (6.75 weeks in average) and the average of daily milk production (MP) was lower in the cows with lower number of births (one to three). This could be influenced also by other factors that affect the restart of the post-partum ovaric cyclical nature (weight changes and diseases during puerperium), according to what was reported by Heppelman et al (2013). The restart of the ovaric post-partum activity is important in milk production because it increases the probability that the animal will present a short interval between the labor and the conception, and, therefore, the economic yield during its productive life could increase (Teyer et al, 2002).…”
Section: Costos De Producciónmentioning
confidence: 72%
“…Lo anterior concuerda con lo observado en este estudio, donde el intervalo parto-estro (IPE) fue más tardío en las vacas primerizas (6.75 semanas en promedio) y el promedio de producción de leche diaria (PL) fue menor en las vacas con menor número de partos (uno a tres). Esto pudo ser influenciado también por otros factores que afectan el reinicio de la ciclicidad ovárica post-parto (cambios de peso y enfermedades durante el puerperio), de acuerdo con lo reportado por Heppelman et al (2013). El reinicio de la actividad ovárica post-parto es importante en la producción de leche porque aumenta la probabilidad de que el animal presente un intervalo corto entre el parto y la concepción, y, de esta manera, se pueda aumentar el rendimiento económico durante su vida productiva (Teyer et al, 2002).…”
Section: Productive Variablesunclassified